A comparative study of the internal law of basic education schools in Syria and France considering total quality management principles - Ghanem, Thanaa (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The aim of this study is conducting a comparison between the internal law of the Syrian basic education schools and the corresponding law in French schools in order to determine the extent to which each law is consisting with total quality management principles, so as to benefiting from French experience in this field. To achieve this aim, a comparative approach is adopted. The results showed that the Syrian internal law has not been designed according to the total quality management principles intentionally, where it focused on some principles and ignored others. For example, it focused on matching student's need as beneficiary, but ignored both graduate's need for work and marketplace itself as beneficiary. In addition, the internal law did not give sufficient importance to supporting top management principle to achieve quality. In contrary, the corresponding French law focuses on the total quality management principles intentionally. Despite not having exactly the same names as mission, the vision and quality councils, even though they are incorporated in the content. It is suggested that there is a need to benefit from strength points in the French law taking into account the Syrian conditions.